KELAYAKAN FINANSIAL PEMBIBITAN DAN BUDIDAYA JARAK PAGAR (JATROPHA CURCAS LINNAEUS) UNTUK MENGHASILKAN CJCO SEBAGAI BAHAN BAKAR YANG RAMAH LINGKUNGAN - Iskandar Muda Purwaamijaya (Universitas Trisakti, 2012)
Energy crisis that attacking violently the earth already pushing efforts increased for benefiting energy that not sources from fossil. Result of physic, chemical, biologic, social and economic analysis got conclusion that Jatropha have better property than others. Research using descriptive method and supported by survey method. Spatial, physic, chemical and biologic analysis done in Bandung District. Objects of research are environmental physic condition in Bandung District, farmers who doing Jatropha seeding and cultivation and cooperative management who supporting activity of Jatropha seeding and cultivation. Research conclusions are : (1) Bandung District have locations where feasible cultivated Jatropha (2) Social and economic condition of farmers communities in locations of Jatropha seeding and cultivation are low and poor. (3) Cost and benefit component of work activity of Jatropha seeding and cultivation from field not enough giving information for feasibility study of finance on effort scale that bigger and more profitable. Next research about financial feasibility study of Jatropha seeding and cultivation must be done so that can be known scale of work that accurate linked with cost benefit components and can be refferenced by stakeholders in Jatropha seeding and cultivation.Keywords : Crisis of energy, Vegetables energy sources, Jatropha seeding and cultivation, Suitability locations, Social and economic condition of farmers, Cost and benefit components, Feasibility study